Coastal Acidification as Nutrients Over Enrichment Impact: A Case Study in Ambon Bay, Indonesia - Idha Yulia Ikhsani; Donna Marselia Siahaya; Frilla Renty Saputra; Sem Likumahua (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2017)
Ambon Bay is a silled bay on Ambon Island consisting of two regions, Inner Ambon Bay (IAB) and Outer Ambon Bay (OAB) that are separated by shallow sill. Ambon bay and its surrounding have economically important ecosystem since the utilization for many activities. The bay is affected by anthropogenic impacts associated with urbanization, climate change, and nutrients over enrichment. The “deep water-rich nutrients” from Banda Sea that enter the bay during Southeast monsoon also contribute to this enrichment as well as the nutrients transport from the land. The high concentration of nutrients increases carbon dioxide level and promotes acidifications. There are literatures about nutrients over enrichment in Ambon Bay, however, little is known about coastal acidification as nutrients over enrichment impact. In order to study the effect of nutrients distribution on the acidity of Ambon Bay, the researchers measured pH and concentrations of nutrients nitrate + nitrite (N+N) and Soluble Reactive Phosphate (SRP) from water samples collected in 7 stations on both IAB and OAB during Southeast monsoon. The results showed that in surface water, nutrients concentrations is increased from May to June due to the “deep water flushing” occurrence on May and increased precipitations from May to June. From July to August, the nutrients concentrations on surface layer decreased, due to the decreased precipitations. In column and bottom water, the nutrients concentrations were increased from May to August. While the acidity have reverse pattern from the nutrients, when nutrient concentrations increased the acidity was decreased. From correlation test, pH was not significantly correlated with the concentrations of nutrients on surface water, but showed significantly correlated on column and bottom water. The results indicated that the distribution of nutrients on column and bottom water might be an important environmental factor affecting the acidification of the Ambon Bay in Southeast monsoon.